Keadilan Restoratif di Persimpangan Jalan : Analisis Implementasi dan Masa Depan dalam Sistem Pidana Kita - Sebastian Yordan Pa; Ni Putu Rai Yuliartini; Dewa Gede Sudika Mangku (Jurnal Hukum dan Sosial Politik, 2026)
This article explores the concept and implementation of restorative justice in Indonesia, an approach currently at a crucial crossroads within the criminal justice system. Rather than solely focusing on punishment, restorative justice offers a path towards repairing relationships between victims, offenders, and the community, seeking solutions oriented around conflict resolution. Through comprehensive analysis, this paper identifies the philosophical foundations and regulations supporting the adoption of restorative justice, while dissecting the dynamics of its application across various levels of legal processes in Indonesia. However, this noble endeavor is not without its challenges, ranging from institutional resistance and uneven understanding to harmonization with the conventional criminal law framework. Behind every case lies a human story yearning for more substantive justice. Therefore, this article argues that the success of restorative justice does not merely lie in its legal umbrella, but in our ability to understand and embrace the human dimension in every dispute resolution process. Consequently, this paper recommends adaptive and collaborative strategies to strengthen the role of restorative justice, ensuring it can guide our criminal justice system towards a more just and dignified future for all parties.